Numerical Study of Epoxy-Ramie Fiber Composite as a Type IV Ballistic Resistant Material - Sutikno Sutikno; Rayhan Fikriandry Rizal; Ahmat Safaat (JMES: The International Journal of Mechanical Engineering and Sciences, 2021)
This paper studies the response of epoxy-ramie fiber composite as ballistic-resistant material using a finite element model. The simulation test was conducted by varying the number of layers and referred to NIJ 0101.06 Type IV as the boundary condition. The model used was a panel made from epoxy-ramie composite laminates with a certain thickness and a 7.62 mm bullet. NIJ states that ballistic material should withstand penetration, and the back-face signature (BFS) should not exceed 44 mm. The impact energy is not briefly mentioned in NIJ failure criteria. The properties of the composite and the bullet were obtained from scientific literature and previous study. The effect of the number of layers on impact response was evaluated by the penetration, deformation, BFS, and absorbed energy.